2015
DOI: 10.1007/s40093-015-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of liquid biofertilizer of brown alga Stoechospermum marginatum on growth, biochemical and yield of Solanum melongena

Abstract: Background Seaweed extracts are used as nutrient supplements, biostimulants and or biofertilizers as an alternative to chemical fertilizers in agriculture. The study was set up to evaluate the biofertilizing efficiency of liquid extracts of brown marine alga Stoechospermum marginatum on growth, biochemical and yield of brinjal, a vegetable crop. To achieve the objectives, liquid extracts at different concentrations were prepared and applied as foliar spray on the brinjal seedlings raised in experimental pots m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 20 publications
(17 reference statements)
2
21
0
4
Order By: Relevance
“…A study carried out with Solanum melongena demonstrated divergent results, where the foliar application of Marginatum stoechospermum shows that the concentration of 1.5% provides increased growth, biochemistry and yield parameters in eggplant due to the presence of elements such as macronutrients and micronutrients, growth hormones, oligoelements and vitamins (Ramya et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A study carried out with Solanum melongena demonstrated divergent results, where the foliar application of Marginatum stoechospermum shows that the concentration of 1.5% provides increased growth, biochemistry and yield parameters in eggplant due to the presence of elements such as macronutrients and micronutrients, growth hormones, oligoelements and vitamins (Ramya et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Seaweed treatment tended to alleviate the inhibitory effect of up to 150 mM NaCl on canola yield. High productivity in response to the treatment with seaweeds was indicated in many plants, such as tomato, chili [34], maize [36], and brinjal [37].…”
Section: Discussionmentioning
confidence: 99%
“…Only U. Lactuca completely alleviated the inhibitory effect of high salt levels on canola plants' endogenous cytokinins content. Cytokinin is a fundamental growth boosting element in chlorophyll biosynthesis and it plays a role in plant growth enhancement [37]. This could explain the higher efficiency of U. lactuca treatment as a bio-stimulant of growth and the chlorophylls' content in canola plants under normal and stress conditions compared to other algal treatments.…”
Section: Discussionmentioning
confidence: 99%
“…SWE had a significant effect on the earliness of flowering, number of flowers, and fruit set percentage in eggplant. Abundant flowering could be the effect of increased vigor of plants [40,54]. SWE foliar spraying increased fruit number and weight of bell pepper [34,52].…”
Section: Effect On Flowering Biology Yield Potential and Fruit Qualitymentioning
confidence: 99%